2015
DOI: 10.5301/ejo.5000691
|View full text |Cite
|
Sign up to set email alerts
|

Ranibizumab versus Bevacizumab for the Treatment of Idiopathic Choroidal Neovascularization: 2-Year Results

Abstract: Bevacizumab and ranibizumab are effective and safe in the treatment of ICNV, with similar effects in improving visual acuity and reducing retinal edema. The long-term efficacy of ranibizumab is superior to bevacizumab in reducing CRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 18 publications
0
10
1
Order By: Relevance
“…Comparative studies have shown promising outcomes of anti-VEGF therapy for ICNV, but few have demonstrated the long-term efficacy [7][8][9][10]. The aim of the present study was to investigate the prognostic factors and incidence of CNV recurrence related to retinal morphological changes of ICNV.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Comparative studies have shown promising outcomes of anti-VEGF therapy for ICNV, but few have demonstrated the long-term efficacy [7][8][9][10]. The aim of the present study was to investigate the prognostic factors and incidence of CNV recurrence related to retinal morphological changes of ICNV.…”
Section: Discussionmentioning
confidence: 94%
“…Currently, there are several available treatment options for ICNV, including intravitreal injection of anti-vascular endothelial growth factor (VEGF) such as ranibizumab, aflibercept and the off-label use of bevacizumab, which has previously been shown to be effective in the treatment of ICNV [7][8][9][10]. Since the majority of ICNV patients are under the age of 50 [11], it is necessary to study the longterm efficiency of this treatment.…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are several available treatment options for ICNV, including intravitreal injection of anti-vascular endothelial growth factor (VEGF) such as ranibizumab, aflibercept and the off-label use of bevacizumab, which has previously been shown to be effective in the treatment of ICNV (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Since the majority of ICNV patients are under the age of 50 (11), it is necessary to study the long-term efficiency of this treatment. The follow-up period in previous studies has been relatively short, usually within 2 years (7,8,10). Therefore, longer follow-up periods were needed for ICNV patients to investigate the prognosis as well as the possibility of disease recurrence.…”
Section: Introductionmentioning
confidence: 99%